NiCr2O4 nanomaterials: Advances in synthesis, modification, and multifunctional applications - Patel, Kajalben; Patil, Mamta; Abhale, Yogita; Chauhan, Ankush; Rana, Garima; Adole, Vishnu; Ban, Tan Kar; Lin, Kun Yi Andrew; Jabir, Majid; Ghotekar, Suresh (Elsevier, 2025)
Many branches of science and engineering now heavily rely on contemporary nanotechnology. Inspired by the magnetic characteristics of nickel chromite nanoparticles (NiCr2O4 NPs), this review examines the structural properties, synthesis methods, and various potential applications. Exploring different synthesis techniques for NiCr2O4 NPs, metal-doped nanoparticles (NPs), and nanocomposites (NCs), it is demonstrated how variables such as the synthesis process and calcination temperature affect the nanoparticles' form (tetragonal or octahedral) and characteristics. Certain structural and functional properties are tailored using processes including sol-gel, co-precipitation, hydrothermal, and combustion. With their spinel structure, NiCr2O4 NPs exhibit promising applications in solar cells, batteries, photocatalysis, sensors, antibacterial agents, anticancer agents, and catalysis. Notably, annealing temperature significantly affects their magnetic behavior and can induce a phase transition from cubic to tetragonal. This review provides a comprehensive analysis of synthesis methods and critical parameters influencing particle size, shape, and functionality, while also highlighting recent advancements and ongoing challenges in harnessing NiCr2O4 NPs for technological and industrial use.